2010
DOI: 10.1016/s1674-8301(10)60028-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of mature miR-21 and miR-155 in cancerous gastric tissues from Chinese patients with gastric cancer

Abstract: ObjectiveMicroRNA (miRNA) expression is deregulated in many types of human cancers. We sought to investigate the expression patterns of the miRNAs, miR-21, miR-145 and miR-155 in sporadic gastric cancer in a Chinese population.MethodsTotal RNA was extracted from archived gastric cancer tissues and adjacent non-cancerous tissues from 20 pairs of paraffin-embedded specimens. Expression levels of miR-21, miR-145 and miR-155 were detected by quantitative reverse transcriptase PCR using a specific stem-loop primer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…In previous studies, miR-155 was overexpressed in cancer tissues of 91 patients by formalin-fixed paraffin-embedded (FFPE) (34), and related to tumor penetration through serosa and lymph node metastasis (35). However, there is also a study on miR-155 significantly downregulated in gastric cancer cell lines compared with GES-1, and overexpression of miR-155 significantly reduced the protein levels of SMAD2 (36).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, miR-155 was overexpressed in cancer tissues of 91 patients by formalin-fixed paraffin-embedded (FFPE) (34), and related to tumor penetration through serosa and lymph node metastasis (35). However, there is also a study on miR-155 significantly downregulated in gastric cancer cell lines compared with GES-1, and overexpression of miR-155 significantly reduced the protein levels of SMAD2 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of miRNAs has been reported for various tumor entities including gastric cancer 7 9 10 . Especially increased expression of miR-21 is identified both in tumor tissues and in blood of GC patients when compared to controls 11 and its oncogenic role has been widely studied 10 12 13 14 . However, the understanding of miRNA deregulation in the stomach related to H.pylori infection and different stages of progression according to Correa's cascade is still preliminary 7 .…”
mentioning
confidence: 99%
“…Although miR-145 expression in GC has been discussed by several authors (25)(26)(27)(28), there is no unified view of the altered expression of miR-145 in scirrhous type GC. To confirm miR-145 expression in GC tissue, we performed qRT-PCR in 20 frozen GC tissue samples.…”
Section: Resultsmentioning
confidence: 99%
“…The apparent discrepancy between the data obtained from scirrhous type GC and other malignancies is worth consideration. It should be noted that these previous reports focused on cancer cells or normal stromal cells and not on peri-tumoral fibroblasts (26)(27)(28)(29)(30)(31). We previously found that the expression of miR-143, co-regulated with miR-145, was localized in fibroblasts of scirrhous type GC and was associated with poor prognosis in the patients with GC (13).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation